ANALISIS KEMAMPUAN PERAWAT DALAM MELAKUKAN BASIC LIFE SUPPORT PADA PASIEN GAWAT DARURAT DI RSU Dr. WAHIDIN SUDIRO HUSODO MOJOKERTO - Lutfi Wahyuni; Agus Haryanto (coba, 2020)
Introduction: Basic Life Support is an effort that must be done immediately by someone if finding victims who experienced cardiac arrest, every health worker must obtained the skilfull ability to provide Basic Life Support (BLS) measures. According to Riskesdas in 2018 the prevalence of cardiovascular disease sufferers in Indonesia is 1.5%. Whereas in the East Java region showed the prevalence of coronary heart disease sufferers at all ages is 1.7. The purpose of this study is to analyze the ability of nurses to implement Basic Life Support in Cardiac Arrest patients. Method: The design used is descriptive analysis. The population is all nurses in the emergency department as many as 45 nurses. The sampling technique used is total sampling. The variable is the ability of nurses in conducting Basic Life Support in Cardiac Arrest patients. The instrument used an SPO Basic Life Support observation sheet. Result: The results showed, most of the respondents did the Basic Life Support action according to the SPO as many as 35 nurses (84.4%), while those who were not performingvaccording to the SPO were 10 nurses (15.6%). Discussion: Basic Life Support is performed on patients who have Cardiac Arrest. Nurses in the emergency room are authorized to conduct Basic Life Support which includes checking consciousness, free airway, cardiac massage,and ventilation.